The effects of high-frequency repetitive transcranial magnetic stimulation on negative symptoms in schizophrenia patients: A systemic review and meta-analysis - Boxing Wang; Xinyue Zhu; Ling Chen; Shuyun Liu; Chengshi Wang (PLoS ONE, 2025)
Objective The research on high-frequency repetitive transcranial magnetic stimulation (rTMS) is very ambiguous, particularly the variability in treatment parameters and the need for standardized protocols, and its effectiveness have hardly been provided conclusive evidence. This systematic review and meta-analysis aimed to determine the effects of high-frequency rTMS on negative symptoms in schizophrenia patients. Methods Six databases (PubMed, Embase, Web of Science, SinoMed, PsycINFO and MEDLINE) were searched from inception to March 2024. Relevant data were extracted and analysed by two independent investigators using Cochrane RevMan software (version 5.3) and R software (version 4.3.1). Results A total of 17 Randomized Controlled Trials (RCTs) were included in the current meta-analysis. Compared with control treatment, active rTMS showed advantage in treating negative symptoms of schizophrenia [standardized mean difference (SMD): −0.22, 95% confidence interval (CI): −0.38, −0.05, P = 0.009; I 2 = 9%]. Subgroup analysis revealed that rTMS with a total treatment course of more than 15 sessions [SMD: −0.31 (95% CI: −0.49, −0.13), P = 0.0007; I 2 = 0%], active rTMS with a frequency of 20 Hz [SMD: −0.40 (95% CI: −0.67, −0.13), P = 0.004; I 2 = 0%], and active rTMS targeting the dorsolateral prefrontal cortex (DLPFC) [SMD: −0.25 (95% CI: −0.40, −0.09), P = 0.003; I 2 = 0%] were significantly effective in terms of reducing negative symptoms. Conclusions The effect of rTMS on negative symptoms is influenced by rTMS parameters. We suggest that researchers should focus on changing the frequency, location and length of treatment to improve negative symptoms of schizophrenia.